Estudio de factibilidad presupuestal para el desarrollo de un proyecto al costo de vivienda tipo interés social en la localidad de Teusaquillo. - Segura Pulido, Paola Andrea; Villalobos Rodríguez, Edisson Alejandro (Universidad Antonio Nariño, 2021)
The development of this research work aims to conclude under a judicious theoretical framework the budgetary feasibility for the development of a project at the cost of low-income housing in the town of Teusaquillo, Bogotá D.C. This perspective allows to know the minimum budgetary panorama for the acquisition of new housing in the locality; this, by optimizing the variables of studies and designs, cost of materials, cost of labor, procedures and licenses.